Women's satisfaction with comprehensive abortion care services and associated factors in central Gondar zone public primary hospitals, northwest Ethiopia, 2023 - Tibebu, Nebiyu Solomon; Alemu, Melaku Birhanu; Rade, Bayew Kelkay; Kassie, Belayneh Ayanaw; Bicha, Mequanint Melesse; Mihret, Muhabaw Shumye; Gedef, Getachew Muluye (Frontiers in Reproductive Health, 2024)
BackgroundAbortion complications are the leading causes of maternal death in low and middle-income countries, including Ethiopia. Providing quality and comprehensive abortion care services is crucial for improving the health of women and increased their satisfaction. Evaluating a client's satisfaction with abortion care is clinically relevant since women's satisfaction with health services is one of the key indicators of high-quality healthcare services. Therefore, this study aimed to assess women's satisfaction with comprehensive abortion care services and associated factors.MethodsAn institution-based cross-sectional study was implemented among 333 women in Central Gondar Zone public primary hospitals from October 1, 2022, to April 30, 2023. Eligible participants were selected using a systematic random sampling technique. The data was collected using an interviewer-administered semi-structured, and pretested questionnaire. STATA version 17 and SPSS version 25 software were used for data entry and analysis respectively. Bivariable and multivariable logistic regression models were used to identify factors associated with clients’ satisfaction with comprehensive abortion care services. A P-value of ≤0.05 with a 95% confidence interval was the cutoff point for determining statistical significance.ResultsThis study revealed that the level of client satisfaction with comprehensive abortion care services was 60.4% (95% CI: 55.0%, 66.0%). The use of abortion medication (AOR = 4.41, 95% CI: 2.59, 7.48), women's age 20–24 years (AOR = 2.94, 95% CI: 1.02, 8.48), and being a student (AOR = 2.88, 95% CI: 1.10, 7.51) were significantly associated with women's satisfaction with comprehensive abortion care services.ConclusionsWomen's satisfaction with comprehensive abortion care services was relatively low, and it was strongly correlated with the method of abortion, age, and occupation. To improve women's satisfaction requires a comprehensive understanding of women's values and perspectives, providing sexual and reproductive health education, and quality abortion care services are recommended.